Study on preparation of modified antifreezing micro-surfacing and its road performance and antifreezing effect. (21st February 2022) - Meng, Yongjun; Ling, Lishan; Lu, Zubiao; Xu, Ruiguang; Zhao, Qixiong; Yan, Tianyi; Fan, Liupeng
Graphical abstract: Highlights: The deicing salt is combined with the micro-surfacing to make the antifreezing micro-surfacing. The performance degradation caused by addition of antifreeze filler on micro-surfacing is alleviated by adding SBR/WER. The abrasion resistance of modified antifreezing micro-surfacing in extreme environment is evaluated. The optimum mixing ratio of SBR/WER modifier is determined. Abstract: In order to solve the problem of road freezing caused by low temperature rain and snow in spring and winter, a kind of micro-surfacing with antifreezing function was prepared in this paper. At the same time, styrene-butadiene rubber (SBR) and waterborne epoxy resin (WER) were used to modify the antifreezing micro-surfacing in order to obtain antifreezing micro-surfacing with better performance. The skid resistance, abrasion resistance and rutting resistance of ordinary antifreezing micro-surfacing (OMS) and modified antifreezing micro-surfacing (MMS) with different content of antifreeze fillers were evaluated by sand patch method, British Pendulum Number (BPN), freeze–thaw cycle wet track abrasion test and rutting deformation test. The antifreezing effects of OMS and MMS were compared by icing test and salt precipitation test under the same amount of antifreeze filler. The road performance test results show that the road performance of antifreezing micro-surfacing decreases with the increase of antifreeze fillers. The skid resistance of MMS under different abrasion degrees, abrasion resistance under extreme freeze–thaw environment and rutting resistance are better compared with OMS. The abrasion resistance and rutting resistance performance have been greatly improved, which effectively reduces the risk of large area aggregate stripping of antifreezing micro-surfacing in its special working and service environment. At the same time, the test results of antifreezing effect show that there is no significant difference in macroscopic antifreezing effect between OMS and MMS. The salt precipitation test indicates that the MMS is beneficial to the sustained release of the effective components of antifreezing. Therefore the MMS can effectively alleviate the deterioration of road performance caused by the addition of antifreeze filler. It is helpful to prolong the service life of antifreezing micro-surfacing and gives full play to the advantages of easy paving and efficient antifreezing. The research on the MMS is of great significance to solve the problem of snow freezing in new and old asphalt pavement.